HLA-Cw6 increases the risk of psoriasis and early onset before twenty-seven years of age among the Vietnamese population - Nhi Thi Uyen Pham; Thuong Van Nguyen; Hao Trong Nguyen (PAGEPress Publications, 2023)
Psoriasis, a chronic inflammatory skin disorder affects people worldwide and is associated with the HLA-Cw6 allele which varies across ethnicities, and is higher in Caucasians than in Asians. We investigated the HLA-Cw6 prevalence in Vietnamese patients with psoriasis and its correlation with onset age and disease severity. We examined the association between HLA-Cw6 and the clinical features in 121 patients with psoriasis and 30 healthy controls and observed that HLA-Cw6 was significantly higher in patients with psoriasis (64.5%) than in the controls (26.7%) (p=0.0001) with an OR of 4.98 (2.04-12.15). The mean age of psoriasis onset was significantly lower in patients with positive HLA-Cw6 than those with negative HLA-Cw6. The AA genotype was more common in patients with mild psoriasis (100%), whereas the TA genotype was prevalent in patients with moderate and severe psoriasis (47.2% and 59.0%, respectively) and in those with high PASI scores (55.1% and 54.1%, respectively). Hence, HLA-Cw6 is a major genetic risk factor for psoriasis in Vietnamese patients, with higher prevalence in patients with early-onset disease. Furthermore, different HLA-Cw6 genotypes are associated with different disease severities.